Personalised care packages for people with rheumatoid arthritis: a mixed-methods study - Heidi Lempp; Arthur Pratt; John D Isaacs; Adam Young; Mwidimi Ndosi; Elena Nikiphorou; Mrinalini Dey; Amanda Busby (RMD Open)
Objectives Disease management in rheumatoid arthritis (RA) requires holistic assessment. We aimed to design personalised care packages suitable for people with RA.Methods This study was conducted using a mixed-methods approach and exploratory sequential design. Consensus workshops were held, involving people with RA and healthcare professionals (HCPs) treating them. Subsequently, an online survey sought views on future care packages for people with RA at relevant disease progression/stages, based on (1) results from previous quantitative data analyses (eg, socioeconomic/clinical factors), and (2) themes identified during workshops.Results Two conceptual care pathways were identified: (1) around the time of RA diagnosis, an early opportunity to influence the disease course; (2) for individuals with established RA, emphasising the importance of ‘the right MDT member at the right time’.Three care packages were suggested: (1) early care package (around RA diagnosis): introduction to MDT; (2) continuity of care package (established RA): primary/secondary providers; and (3) personalised holistic care package: integral to packages 1 and 2, implemented alongside allied health professionals.The survey received 41 responses; 82.9% agreed that people with RA need a consistent ‘early care package’ at diagnosis. 85.4% approved of additional care packages tailored to individuals’ clinical, psychological and social needs when moving to different stages of their long-term disease. Fleiss’ Kappa calculations demonstrated fair level of agreement among respondents.Conclusion Two care pathways, with three tailored care packages, were identified, with potential to improve management of people with RA. Future research will help to determine if such care packages can impact clinical (including patient-reported) outcomes.